Proceedings of the ACM Internet Measurement Conference 2020
DOI: 10.1145/3419394.3423666
|View full text |Cite
|
Sign up to set email alerts
|

Easing the Conscience with OPC UA

Abstract: Due to increasing digitalization, formerly isolated industrial networks, e.g., for factory and process automation, move closer and closer to the Internet, mandating secure communication. However, securely setting up OPC UA, the prime candidate for secure industrial communication, is challenging due to a large variety of insecure options. To study whether Internet-facing OPC UA appliances are configured securely, we actively scan the IPv4 address space for publicly reachable OPC UA systems and assess the securi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 46 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Since traditional industrial communication protocols, e.g., Modbus, were designed for communication in isolated environments, their design does not include any security mechanisms (Dahlmanns et al 2020). Furthermore, especially older embedded industrial devices often lack the computational resources to perform state-of-the-art cryptography operations, which becomes particularly problematic in the face of the upcoming shift toward post-quantum cryptography (Henze 2020).…”
Section: Network Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Since traditional industrial communication protocols, e.g., Modbus, were designed for communication in isolated environments, their design does not include any security mechanisms (Dahlmanns et al 2020). Furthermore, especially older embedded industrial devices often lack the computational resources to perform state-of-the-art cryptography operations, which becomes particularly problematic in the face of the upcoming shift toward post-quantum cryptography (Henze 2020).…”
Section: Network Securitymentioning
confidence: 99%
“…However, security analyses indicate that 42 % of all TLS-enabled industrial protocol deployments on the Internet, i.e., deployments which are reachable in the IPv4 address space, show security deficits (Dahlmanns et al 2022). Additionally, although OPC UA, the most promising modern industrial communication protocol, was designed with security in mind, research shows that 92 % of the Internetreachable OPC UA deployments are configured with security deficits (Dahlmanns et al 2020).…”
Section: Network Securitymentioning
confidence: 99%
“…For the IoT and IIoT, research revealed many deployments relying on vulnerable software [6,30,46] and communicating without any security mechanism [12,57,59,60,83], e.g., access control. Even with built-in security features, operators often configure such services insecurely [11]. For example, a massive reuse of certificates was traced back to a Docker image including certificates and corresponding private keys [12] jeopardizing the authenticity of numerous deployments.…”
Section: Related Workmentioning
confidence: 99%
“…Our search terms (which we elaborate in more detail in Appendix B) build two query groups (Table 1 (left)); Standard comprises mainstream communication protocol names [68] and frequently used technologies [74] for a wide analysis of images referencing current issues. For comparison and more focusing on a specific area, we choose the Industrial Internet of Things (IIoT) as past studies showed a great susceptibility to security faults [11,12,35,53,59,60], i.e., IIoT includes protocol names from this area.…”
Section: Retrieving Images From Docker Hubmentioning
confidence: 99%
See 1 more Smart Citation